A indústria 4.0 no agronegócio: o nascimento de uma spin-off para gestão da manutenção de máquinas e implementos agrícolas - Assis, Priscila Bittencourt de (2019)
This project presents the steps developed by Metalquip to analyze, plan, develop and application an innovative solution for preventive / predictive maintenance of agricultural machinery and equipment, as well as the process of creating a corporate spin-off to take advantage of the identified opportunity. The work follows the technological report protocol proposed by Marcondes, Miguel, Franklin and Perez (2017), starting from the generation of the idea, pre-validation of the solution with clients, followed by procedures for internal approval with the board, approval of the budget for the pilot project development, patenting of the solution: as a utility model - BR 10 2018 010513 2, creation of the spin-off company and an action plan (in execution) for project implementation. The project's contributions include the development and application of an innovative technological solution for the Brazilian market, providing productivity gains for sugar and alcohol plants, with potential for expansion in other sectors of industry such as mining, construction, oil and gas and aviation. The solution encompasses not only results in terms of technology and business development, but also brings environmental benefits, by reducing oil leaks in the field. It is also understood that the project portrays a peculiar but potentially replicable reality for other industries of industrial components, adding important learning that can serve as a reference for entrepreneurs and academics.